Practical tips for developing your staff - Pratchett, Tracey; Young, Gil (Practical tips for library and information professionals., 2016)
This book offers innovative tips and tried-and-tested best practice to enable library and knowledge workers to take control of professional development regardless of the budget and time available to them. Continuing professional development (CPD) is a key component of a successful and satisfying career. Part of the Practical Tips for Library and Information Professionals series, this book offer a wide range of ideas and methods for all library and information professionals to manage the development of those who work for and with them. You will find flexible tips and implementation advice on topics including: enabling others to plan, reflect on and evaluate their personal development appraisals and goal setting: linking personal objectives to organizational objectives performance management sourcing funding to attend and run events planning formal development activities such as courses and conferences accessing informal activities using social media as a development tool role of professional bodies and networks mentoring, buddying and coaching networking. Readership: All library and information professionals who have responsibility for managing, mentoring and training staff and individuals wishing to manage their own CPD.